Goat Farm Information Management System - Sivakumar, Sharveena; Nureize Arbaiy, (Applied Information Technology And Computer Science, 2025)
Goat farming is one of the main livestock industries in Malaysia that supplies the country's meat supply. Most goat farms, especially the smaller ones, keep their farm data manually despite technological advancements. Manual recording techniques are employed, along with file and book approaches. Even though farming activities can still be managed using this method, there are several drawbacks. These include the potential for calculation or data transfer errors, lengthy data entry procedures, and slow record searches. To address this issue, a web platform namely the "Goat Farm Management System" has been built. The plan aims to use digital and web technologies for the management of related livestock farm tasks and records. It optimizes computerized systems for efficient farm management and was built with PHP and MySQL.  Agile methodology is employed in the development. The system's main features are registration, goat information management, buy and sales records, reporting, and administrative tasks. The system provides farm staff with the functionality to record and access goat herd data, goat herd health records and financial tracking. This digital transformation will help the goat farming business by increasing output and sustainability. By using this strategy, the Malaysian goat farming industry may embrace technology and overcome the challenges posed by manual data management.